Proceedings of the 18th ACM Conference on Innovation and Technology in Computer Science Education 2013
DOI: 10.1145/2462476.2462501
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding students' learning using test my code

Abstract: As programming is the basis of many CS courses, meaningful activities in supporting students on their journey towards being better programmers is a matter of utmost importance.Programming is not only about learning simple syntax constructs and their applications, but about honing practical problem-solving skills in meaningful contexts. In this article, we describe our current work on an automated assessment system called Test My Code (TMC), which is one of the feedback and support mechanisms that we use in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(53 citation statements)
references
References 17 publications
0
53
0
Order By: Relevance
“…• Automatic assessment tools (e.g., BOSS, CourseMarker, Web-CAT, and Test My Code [32,45,24,89]) that manage and grade student programming assignments submissions.…”
Section: Defining Smart Learning Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…• Automatic assessment tools (e.g., BOSS, CourseMarker, Web-CAT, and Test My Code [32,45,24,89]) that manage and grade student programming assignments submissions.…”
Section: Defining Smart Learning Contentmentioning
confidence: 99%
“…Test My Code [89] is a service that is used to both assess students' work and to scaffold students as they are working on programming assignments. The service contains backend services that are used to provide scoreboard details, create courses, create embeddable questionnaires, monitor students' progress, create code reviews, and store snapshot data from the students progress.…”
Section: A22 Test My Codementioning
confidence: 99%
“…In our earlier XA-based courses [11], the feedback has been provided by human advisors (teachers). In the MOOC, the participants program in an industry-standard programming environment that contains a plugin, which provides help for the students (for additional details, see [18]). …”
Section: Course Content and Pedagogymentioning
confidence: 99%
“…Most AATs accept and run student-provided source code, but some assess code tracing, promote good style techniques, or encourage a test-driven approach. In our review of existing literature, we found data relevant to our research questions for these tools: Aari, 1 Athene, 2 Autograder, 3 AutoLep, 4 Automatic Marker, 5 BlueFix, 6 BOSS, 7 CAP, 8 Ceilidh, 9 COALA, 10 CodeWrite, 11 CourseMarker, 12 Curator, 13 JUG, 14 Mooshak, 15 PGSE, 16 Retina, 17 Style++, 18 Submit, 19 Test My Code, 20 TRAKLA, 21 TRAKLA2, 22 Trillium, 23 and Web-CAT. 24 We recognize that published research exists on many comparable tools, but we did not readily find data that addressed our questions.…”
Section: Related Workmentioning
confidence: 99%
“…20 In times they would have normally been grading, instructors were available to help students and complete various work-related responsibilities. Additionally, since teaching assistants no longer had to assist with grading, TAs could gain more experience tutoring students who needed assistance.…”
Section: Instructor Perceptions Of Automated Assessment Toolsmentioning
confidence: 99%